An Experimental Study on Industrial Concete Pile Foundation in Soft Soil: Comparison of Monolithic and Pile with Welded Joints - Effendi, Rustam; Pratiwi, Ade Yuniati; Chairunnisa, Nursiah; Alpindi, Nor Muhammad; Nurwidayati, Ratni; Krasna, Wiku Adhiwicaksana (Engineering, Technology & Applied Science Research, 2024)
This study presents an experimental investigation into the industrial foundation piles. The research carried out employed both destructive and non-destructive testing methods to evaluate the concrete compressive strength and flexural strength capacity of the piles under monotonic loading. The Destructive Test (DT) involves a 28-day cylinder concrete compressive test, while the Non-Destructive Test (NDT) utilizes the Ultrasonic Pulse Velocity (UPV) and Rebound Hammer (RH) tests. The flexural strength test is conducted using a loading frame, and the results are compared to the GeoPIV-RG, which measures the displacement during the test. The experimental investigations provide insights into the behavior of pile joints when subjected to monotonic load in soft and loose soil. The results indicate a significant difference between the compressive strength obtained from the DT and NDT, with a ratio of 0.64-0.74. Furthermore, the failure occurred at the joints, rather than the welded area, with the ratio of the initial stiffness of the piles with joints to the monolithic pile being 0.15 for zig-zag welded and 0.30 for circular welded, and reaching an average value of 0.225. According to the GeoPIV-RG result, the displacement is similar to the flexural strength test result.